Spontaneous ruptured pyomyoma: A rare yet critical postpartum complication: A case report - Soo, Tze Hui; Subramaniam, Mogana; Chai, Woon Kian; Ee, Wei Sheun (Elsevier, 2024)
Pyomyoma, a rare complication of leiomyoma, presents a unique clinical challenge due to its infrequency with potentially fatal complications. Herein, we report the case of a 44-year-old Para 3+1 woman with red degeneration of uterine fibroids during pregnancy, who experienced worsening abdominal pain and foul smelling vaginal discharge 1 week post Caesarean section. Despite hemodynamic stability, her septic markers were markedly raised. A bedside ultrasound noted a pelvic complex cystic collection, further confirmed on CT scan as spontaneous ruptured of pyomyoma complicated by complex fistulas with surrounding organs. She underwent total abdominal hysterectomy and abdominal washout the next day, with intravenous antibiotic on-board. Histology examination confirmed acute suppurative inflammation of the uterine fibroid with endometritis. This case report contributes to the existing medical literature by shedding light on a rare and potentially life-threatening leiomyoma complication. Its potential to mimic acute puerperal endometritis, makes its diagnosis especially challenging, necessitating a high index of suspicion. © 2024